External Assurance and Anti-Corruption Disclosure: Evidence from the Early Adoption of Materiality-Centered Sustainability Reporting - Rahmatdi Rahmatdi; Dany Adi Saputra (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2026)
This study examines whether externally assured sustainability reports (SRs) are more likely to provide greater anti-corruption disclosure when stakeholder attention to corruption is higher. The study is set in the context of the early adoption of materiality-centered sustainability reporting, focusing on the period immediately following the introduction of GRI G4 (2013) — the first sustainability reporting framework to formally position materiality as the cornerstone of determining report content. Drawing on stakeholder theory and the materiality principle, this study stipulates three factors that may raise stakeholders’ attention to the corruption issue: industry corruption risk, country-level pressures on corruption (home-country corruption risk and home-country anti-corruption enforcement), and global pressure on corruption. By employing OLS regression with two groups of samples: 185 externally assured SRs and 145 non-assured SRs drawn from the GRI G4 early adoption years (2014–2015), this study finds that external assurers may play a role in promoting greater anti-corruption disclosure when companies face greater country-level and global pressure on corruption. However, this study finds no evidence of external assurers' role in the presence of higher industry corruption risk. Instead, the relation between industry corruption risk and anti-corruption disclosure is stronger when SRs are not externally assured. The findings contribute to the literature on sustainability assurance and the implementation of the materiality principle under GRI G4.